The potential integration of Simodont® Dental Trainer in different stages of the dental curriculum - Mahmoud M. Bakr; Ghassan Idris; Mahmoud Al Ankily (Elsevier, 2024)
Background: The lack of standardised studies remains an obstacle to developing a consistent approach to integrating virtual dental simulation (VDS) into dental education. The aim of this study was to develop consensus among experienced educators and dental practitioners on the optimal integration of VDS at various stages of dental curricula. The goal was to propose clear yet flexible recommendations that could be implemented by most educational institutions. Methods: Focus groups were established, consisting of experienced academic educators involved in VDS, experienced academic staff who had not previously been involved in VDS, and experienced dental practitioners. These groups exchanged ideas about the best ways to integrate VDS into dental curricula. The Simodont® Dental Trainer system was used to design a curriculum for VDS. Results: The expert group agreed that VDS for manual dexterity exercises should be introduced in the first year of dental curricula. This should be followed by cariology exercises in the second year and crown preparation exercises in the third year, alongside traditional manikin-based simulation exercises. Additionally, VDS was recommended for senior students on an ad hoc basis for academic recovery purposes. However, VDS endodontic exercises were excluded from the proposed integrative dental curriculum. Other ways of utilising VDS were identified, such as student recruitment activities and intensive refreshment programs at the start of each academic year. Conclusions: This study proposes a flexible approach to including VDS in dental curricula. This proposed approach can be customised to meet the specific needs of each educational institution, providing a tailored learning experience for students.